MODEL SNOWBALL THROWING: STRATEGI MENINGKATKAN KETERAAMPILAN BERBICARA DALAM PEMBELAJARAN - Sri Mulyani Rusli; Siti Lutfiyah; Vani Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking is a core competency in language learning that students often struggle to master due to a lack of confidence and limited oral expression. The Snowball Throwing model, as a cooperative learning strategy, offers an interactive approach to address this challenge. Through a literature review, this article examines the theoretical basis, implementation steps, benefits, and challenges of the Snowball Throwing model in improving students' speaking skills, based on academic literature. The purpose of this study is to improve students' speaking skills using the Snowball Throwing learning model and to determine students' responses to the Snowball Throwing learning model in Indonesian language learning.